Maori Television: The First Ten Years - Smith, Jo (Auckland University Press, 2016)
Established in 2004, Maori Television has had a major impact on the New Zealand broadcasting landscape. But over the past year or so, the politics of Maori Television have been brought to the foreground of public consciousness, with other media outlets tracking Maori Television's search for a new CEO, allegations of editorial intervention and arguments over news reporting approaches to Te Kohanga Reo National Trust.Based on a Marsden Grant and three years of interviews with key stakeholders – staff, the Board, other media, politicians, funders and viewers – this is a deep account of Maori Television in its first ten years. Jo Smith argues that today's arguments must be understood within a broader context shaped by non-Maori interests. Can a Maori broadcaster follow both tikanga and the Broadcasting Standards Authority? Is it simply telling the news in Maori, or broadcasting the news with a Maori perspective? How can it support te reo Maori at the same time as appeal to all New Zealand? How does it function as the voice of its Maori stakeholders?Offering five frameworks to address the challenges of a Maori organisation working within a wider non-Maori context, this is a solidly researched examination of Maori Television's unique contribution to the media cultures of Aotearoa New Zealand.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 3-Océanie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; Nouvelle-Zélande/Aotearoa (corpus analysé); Nouvelle-Zélande/Aotearoa (lieu de production du savoir); _Nettoyé

NZ Idol: Nation Building Through Format Adaptation - De Bruin, Joost (Global Television Formats: Understanding Television Across Borders, 2012)
Three seasons of NZ Idol , the New Zealand adaptation of the global Idols format, were aired on public broadcaster TVNZ’s channel TV2 in 2004, 2005 and 2006. The ﬁnal episode of the ﬁrst season was the most-watched television programme in New Zealand in 2004, with 1.4 million people, a third of the New Zealand population, tuning in (South Paciﬁc Pictures, 2004). In terms of ratings NZ Idol has been one of the most successful locally made television programmes of the last decade. At ﬁrst glance, NZ Idol has also been very successful in representing ethnic and cultural diversity. In the auditions phase of the show young New Zealanders of 16 years plus from a range of backgrounds are featured, and in the subsequent phases the audience gets to know a selection of them intimately. The winners of all three seasons (Ben Lummis in season 1, Rosita Vai in season 2, and Matt Sounoa in season 3) have Paciﬁc Island roots, and as a result three young “brown” people were crowned “New Zealand Idols.” This is remarkable, since according to a previous study by Misha Kavka (2004: 231) non-white people have largely been absent from New Zealand reality TV programmes. A closer look suggests, however, that featuring contestants from different cultural backgrounds in NZ Idol generally serves a particular nation building agenda that New Zealand is heavily involved in as a postcolonial society, in which ethnic minorities are subjected to representations that favour the interests of dominant cultural groups. The aim of this nation building agenda is to establish a new and distinct sense of national identity which will set New Zealand apart from Britain, the former colonial power, and other English-speaking nations.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Océanie (corpus analysé); 4-Océanie (lieu de production du savoir); Aotearoa/Nouvelle-Zélande (corpus analysé); Aotearoa/Nouvelle-Zélande (lieu de production du savoir); _Nettoyé

Global Television: An Introduction - Barker, Chris (Wiley-Blackwell, 1997)
This text provides readers with useful summaries and evaluations of key arguments relating to the development of television as an industry across the globe and its potential cultural impact. There is a continual insistence in the book on the need to connect issues of industry with those of culture.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); _Nettoyé